The 2025 Trade War: Dynamic Impacts Across U.S. States and the Global Economy - Andrés Rodríguez-Clare; Feodora A. Teti; Mauricio Ulate; Jose P. Vasquez; Roman D. Zarate (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
We use detailed tariff data and a dynamic trade and reallocation model with downward nominal wage rigidities to quantitatively assess the economic consequences of the recent increase in U.S. import tariffs and the responses of its trading partners. Higher tariffs trigger an expansion in U.S. manufacturing and agricultural employment, but this comes at the expense of a decline in service employment, with overall employment declining as lower real wages reduce labor-force participation. For the United States as a whole, real income falls around 0.1% by 2028, the last year we assume the high tariffs are in effect. Importantly, our analysis disaggregates the U.S. into its 50 states, while incorporating cross-state redistribution of the tariff-generated fiscal revenue, allowing us to analyze which states gain or lose more from the shock. Some of the most populous states, like California, New York, and Texas, suffer real income declines of up to 1.4%. On the flip side, 34 states gain, in some cases as much as 1.9%. Turning to cross-country results, some close U.S. trading partners - like Canada, Mexico, and Ireland - suffer the largest real income losses.
Keywords: F10; F11; F13; F16; F40; F42; 330; tariff changes; U.S. Tariffs; liberation day; canada; Mexico; China